Identification of material properties of composite materials using nondestructive vibrational evaluation approaches: A review - Tam, J.H.; Ong, Z.C.; Ismail, Z.; Ang, B.C.; Khoo, S.Y. (Taylor & Francis, 2017)
Destructive identification approaches are no longer in favor since the advent of nondestructive evaluation approaches, as they are accurate, rapid, and cheap. Researchers are devoted to improving the accuracy, rate of convergence, and cost of such approaches, which depend greatly on the types of vibrational experiments conducted and the types of forward and inverse methods used in numerical section. Therefore, this article presents a review on the development of nondestructive vibrational evaluation approaches in identifying the elastic constants of composite plates, in experimental and numerical manners in order to enlighten researchers with the current trends of nondestructive vibrational approaches.